1975
DOI: 10.1902/jop.1975.46.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Observations Following Root Amputation in Maxillary Molar Teeth

Abstract: Thirty-four maxillary molar teeth were evaluated from 11 to 84 months after root amputation. The most consistent finding was that although 24 were neither splinted nor supported in any way, only three developed mobility. Two of these were used as abutments for partial dentures. One other tooth was extracted due to recurrent lateral abscesses and subsequent involvement of the mesial furca.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
5

Year Published

1987
1987
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 3 publications
1
25
0
5
Order By: Relevance
“…The authors attributed their success to the elimination of plaque retentive areas in the furcations, meticulous patient oral hygiene, and regular maintenance care. Klavan (1975), reported that only one of 34 root‐resected maxillary molars were extracted after 3 years, and that was due to a periodontal abscess. Erpenstein (1983), reported only 3 of 34 root‐resected teeth (9%) followed for 4–7 years were lost for periodontal reasons (2 due to pocketing and 1 due to excessive mobility).…”
Section: Growth Factorsmentioning
confidence: 99%
“…The authors attributed their success to the elimination of plaque retentive areas in the furcations, meticulous patient oral hygiene, and regular maintenance care. Klavan (1975), reported that only one of 34 root‐resected maxillary molars were extracted after 3 years, and that was due to a periodontal abscess. Erpenstein (1983), reported only 3 of 34 root‐resected teeth (9%) followed for 4–7 years were lost for periodontal reasons (2 due to pocketing and 1 due to excessive mobility).…”
Section: Growth Factorsmentioning
confidence: 99%
“…The effect of periodontal therapy on the survival of multi-rooted teeth with furcation involvement has been systematically reviewed (Huynh-Ba et al 2009), and this review concluded that good long-term survival rates could be achieved. There has been a great variation reported for the survival data of teeth after resective treatment (Bergenholtz 1972, Hamp et al 1975, Klavan 1975, Langer et al 1981, Erpenstein 1983, Bu¨hler 1988, Basten et al 1996, Blomlof et al 1997, Carnevale et al 1998, Dannewitz et al 2006). There has been a great variation reported for the survival data of teeth after resective treatment (Bergenholtz 1972, Hamp et al 1975, Klavan 1975, Langer et al 1981, Erpenstein 1983, Bu¨hler 1988, Basten et al 1996, Blomlof et al 1997, Carnevale et al 1998, Dannewitz et al 2006).…”
mentioning
confidence: 99%
“…1998). Furthermore, Klavan (1975) demonstrated that the removal of one root of a maxillary molar did not increase the mobility of a tooth in normal function.…”
Section: Discussionmentioning
confidence: 99%